Screening of antibacterial and antioxidant activities of marine fungi isolated from the North Sea of Vietnam - Ngo , Thi Duy Ngoc; Phan , Thi Hoai Trinh; Dinh, Thanh Trung; Yurchenko, Anton N.; Huynh , Hoang Nhu Khanh; Le , Dinh Hung; Vo , Thi Dieu Trang; Le, Thi Hoa; Pham, Duc Thinh (Vietnam Journal of Marine Science and Technology, 2023)
Marine fungi are recognized as a rich source of pharmacologically active secondary metabolites, different from terrestrial fungi. This study aimed to assess the antimicrobial and antioxidant activities of 61 marine fungal strains isolated from 34 samples collected in the research journey of the Akademik Oparin vessel in the North Sea of Vietnam in 2021. Of these, 23 were from sponges, 21 from seaweeds, 15 from sediments, and only 2 from seawater. The antimicrobial screening results showed that 75.4% (n = 46) of fungal strains exhibited inhibitory activity against at least one test microorganism. The antioxidative properties results indicated the capacity for free DPPH (2,2-diphenyl-1-picrylhydrazyl) and ABTS (2,2’-azino-bis(3-ethylbenzothiazoline-6-sulphonic acid) radical scavenging of crude extracts with 32.7% (n = 20) and 93.4% (n = 57), respectively. Six isolates with potent antibiotic and antioxidant activities were identified as belonging to the phylum Ascomycota and affiliated with five genera. Our findings indicated that these marine fungi could be impressive sources of multi-functional bioactive compounds and may find applications in the pharmaceutical industry.